2005
DOI: 10.1097/01.olq.0000158496.00315.04
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis and Neisseria gonorrhoeae Prevalence and Coinfection in Adolescents Entering Selected US Juvenile Detention Centers, 1997–2002

Abstract: Chlamydia and gonorrhea prevalence was very high in females in all project sites. In males, chlamydia prevalence was high in some areas; however, gonorrhea prevalence was substantially lower. These prevalence data justify screening for chlamydia and gonorrhea among female adolescents in juvenile detention centers nationally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
62
0
4

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 15 publications
5
62
0
4
Order By: Relevance
“…En cuanto a la relación entre las variables relativas a los hábitos sexuales y la presencia de C. trachomatis, fue significativa la encontrada entre el consumo de alcohol o drogas durante la última relación sexual (p=0,048) y tener parejas con alguna infección diagnosticada de transmisión sexual (p=0,006) (cuadro 4). (9). En dos estudios llevados a cabo en Chile entre mujeres adolescentes internadas en hospitales, se encontraron prevalencias de 6,9 y 7,9 % para la infección por C. trachomatis y no se detectaron casos de infección por N. gonorrhoeae (32,33); y en otro estudio hecho en Argentina en la misma población, la prevalencia de infección por C. trachomatis fue de 9,5 % (34), valores estos que superan los registrados en este estudio.…”
Section: Análisis Estadísticounclassified
See 2 more Smart Citations
“…En cuanto a la relación entre las variables relativas a los hábitos sexuales y la presencia de C. trachomatis, fue significativa la encontrada entre el consumo de alcohol o drogas durante la última relación sexual (p=0,048) y tener parejas con alguna infección diagnosticada de transmisión sexual (p=0,006) (cuadro 4). (9). En dos estudios llevados a cabo en Chile entre mujeres adolescentes internadas en hospitales, se encontraron prevalencias de 6,9 y 7,9 % para la infección por C. trachomatis y no se detectaron casos de infección por N. gonorrhoeae (32,33); y en otro estudio hecho en Argentina en la misma población, la prevalencia de infección por C. trachomatis fue de 9,5 % (34), valores estos que superan los registrados en este estudio.…”
Section: Análisis Estadísticounclassified
“…La infección por C. trachomatis puede ser asintomática en el 70 % de las mujeres y, por lo menos, en 50 % de los hombres (11), en tanto que la causada por N. gonorrhoeae puede cursar asintomática en una gran proporción de mujeres (12) y suele ser más sintomática en los hombres (13). Asimismo, se ha encontrado una frecuencia de hasta 50 % de infección simultánea por ambos microorganismos (9,14).…”
unclassified
See 1 more Smart Citation
“…For example, whereas Barbosa et al reported a coinfection prevalence of 4.4% in Brazil [121], Papadogeorgakis et al found gonococcal coinfection in 30% of the C. trachomatis-infected patients in Greece [122]. Kahn et al found that 51% of males with gonorrhea were coinfected with chlamydia in US juvenile detention centers [123]. Thus, most of the studies are geographically limited and targeted to a certain portion of the population.…”
Section: Trachomatis Coinfections and Male Infertilitymentioning
confidence: 99%
“…Both PID and epididymitis can result in infertility. In addition, investigations indicate that the presence of Chlamydia infection increases the risk of HIV transmission (Fleming and Wasserheit 1999;Kahn et al 2005). Chlamydia is also known as a ''silent'' disease since 75 % of infected women and at least 50 % of infected men have no symptoms.…”
Section: Introductionmentioning
confidence: 99%